Building Islamic Character in Students Through the One Day Boarding Program: Pembentukan Karakter Islami Siswa Melalui Program One Day Boarding - Fahyuni, Eni Fahriyatul; Wijayanto , Anang (Adabiyah: Jurnal Pendidikan Islam, 2025)
General background: The current era presents significant moral challenges, highlighting the critical role of character education in preparing students for a valuable life in society. Specific background: This study investigates the "One Day Boarding" program at Muhammadiyah Middle Schools and MTs in Sidoarjo, which aims to form and strengthen students' Islamic character based on the Qur'an and Sunnah. Knowledge gap: While the importance of character education is well-established, there is limited specific research on how a specialized "one day boarding" model is systematically implemented to achieve this goal within an Islamic school context. Aims: This research explores the concept and implementation of the program and its role in building students’ Islamic character. Results: The findings show that the "One Day Boarding" program is implemented through a systematic, integrated approach that includes religious practices and character-building activities. It successfully integrates cognitive, affective, and psychomotor domains. Novelty: This research provides a detailed, qualitative case study of a specific character-building program, offering a practical model for other educational institutions. Implications: The findings suggest that a structured program, supported by curriculum integration and dedicated educators, can effectively address the need for moral and religious character formation. Highlights : Program One Day Boarding is a systematic approach to character formation. The program successfully integrates cognitive, affective, and psychomotor domains. The program's success is supported by a strong curriculum and dedicated teaching staff. Keywords: One Day Boarding, Islamic Character, Muhammadiyah, Character Education, Sidoarjo